Sustainability Status of Floating Net Cage Aquaculture (KJA) in Jatiluhur Reservoir, Purwakarta Regency - Megawati Arsita Putri (Graduate School Bogor Agricultural University (SPs IPB), 2019)
The development of floating net cage aquaculture (KJA) in Jatiluhur Reservoir needs to pay attention to five dimensions of sustainable development (ecological, economic, socio-cultural, institutional and technological) to avoid problems arising from the KJA aquaculture activities, sustainable management is needed in order to optimize the benefits that can be obtained from KJA aquaculture activities. The purpose of this study was to analyze and assess the sustainability of KJA fisheries in the Jatiluhur Reservoir using the Rapid Apprisial Fisheries (RAPFISH) application with the MDS (Multi Dimensional Scaling) system approach. The results of the sustainability analysis of KJA aquaculture fisheries in Jatiluhur Reservoir showed quite sustainable with an index value of 51.33%, a stress value of 13.22% and a R2 value of 95.65%. Based on the leverage analysis to determine the most sensitive attributes as lever attributes that are used to improve the sustainability of KJA aquaculture, there are 8 key attributes as sensitive attributes including aquatic fertility, market ease, labor wages, space conflicts, business ownership, law enforcement, size selection and thinning, hatchery technology.